HUBUNGAN SANITASI LINGKUNGAN DAN PENYAKIT INFEKSI DENGAN STATUS GIZI ANAK BALITA DI KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA - , Andi Tenri Abang ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Undernourishment is a problem of public health commonly encountered in developing countries. Almost 50% of 10-11 millions of underfives mortality from causes that are preventable. District of Kutai Kartanegara is known as the most wealth of district in Indonesia